Adaptability of the Cutter-Head of the Earth Pressure Balance (EPB) Shield Machine in Water-Rich Sandy and Cobble Strata: A Case Study - Chaodong Wan; Zhiyi Jin (Advances in Civil Engineering)
Earth Pressure Balance (EPB) shield machines are considered to be the most efficient tunneling method for Metro tunnels due to their adaptability to a great variety of ground conditions, higher construction efficiency, and providing a safer working environment. There are many guidelines available for EPB shield machine selection. However, these guidelines are very general and cannot be used directly for an upcoming project. This paper takes Chengdu Metro Line 6 in China as the engineering background; the studied area is typical of a water-rich sandy and cobble stratum with high content of cobble. Three types of EPBs in the two continuous intervals exhibit significant differences in performance and encounter many difficulties such as wear of the cutter disc and tools, clogging, and severe surface settlement during the operation. These difficulties prevent the construction efficiency, increase the cost of the project, and cause delays in construction period. The causes of these difficulties are summarized by recording and comparing the operational parameters of the three types of EPBs. These parameters that are summarized include the advance rate, total thrust, torque, and the rate of rotation of the cutter-head. In addition, the surface settlements are also compared. The results indicate that the opening rate, maximum opening size, and the opening position of the cutter-head are key factors that affected the geological adaptability of the shield machine in water-rich sandy and cobble strata. Among the three factors, the maximum opening size and opening position are the most important factors influencing the strata adaptability of the cutter-head. To avoid frequent jams of the cutter-head, the maximum torque should be not less than 6,500 kNm. The maximum opening size should not be less than 420 mm × 420 mm. The effect of increasing the central opening of the cutter-head is that large cobbles and boulders can be discharged through the central opening when they cannot be discharged through the opening near the original position of the cobbles and boulders. This paper provides specific guidance on the selection of cutter-head for shield machines in water-rich sandy and cobble strata.